(untitled) (Texas Journal of Medical Science, 2023)
On white male rats on the model of acute medicinal hepatitis induced by paracetamol, the hepatoprotective property of the gum resin of ferula asafoetid and Legalon was tested. It has been established that the gum of the ferula asafoetida resin is not inferior to Legalon in its pharmacological activity. It is believed that the use of ferula asafoetid resin gum as a hepatoprotector, like Legalon, will increase the effectiveness of therapeutic measures for acute medicinal hepatitis and reduce its complications